Analisis Efesiensi Dan Efektivitas Pengelolaan Pendapatan Daerah Dalam Meningkatkan Pertumbuhan Ekonomi Kota Tidore Kepulauan Tahun 2020-2021 - Putri, Nahara Jelita; Hasan, Muhammad Hi; Majojo, Muhammad Yasin (Peneliti.net, 2025)
This study aims to analyze the efficiency and effectiveness of Regional Revenue management—which includes the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Regional Original Income (PAD)—and their contribution to the economic growth of Tidore Islands City in the 2020–2024 period. The study uses a qualitative method with efficiency ratio and effectiveness ratio analysis techniques based on budget realization data obtained from the Tidore Islands City BPKAD. The study results show that all components of regional revenue are inefficient, characterized by an efficiency ratio above 100 percent, reflecting high regional spending compared to revenue received. Conversely, the effectiveness level shows relatively good results, particularly the General Allocation Fund (DAU), which annually reaches its target and is in the effective category. The effectiveness of the Special Allocation Fund (DAK) and Regional Original Revenue (PAD) fluctuates but remains in the moderately effective to very effective category in some years. Regional economic growth shows a positive trend, particularly in 2024 with an achievement of 6.40 percent, although it is not yet fully supported by fiscal independence. These findings indicate that the economic growth of Tidore Islands City is more influenced by the effectiveness of budget absorption than the efficiency of its management. Thus, increasing the efficiency of regional revenue management is an important strategy to strengthen fiscal independence and encourage sustainable economic growth.